Design and Development of a Freelance Sport Coach Mobile Application - Lieu, Yee Zhe; Wahid, Norfaradilla (Applied Information Technology And Computer Science, 2024)
The growing interest in sports has led to a surge in demand for sports coaches, resulting in popular mobile applications for finding virtual courses. However, there are limited application for booking physical courses. This application fills the gap by offering a physical coach and trainee matching platform specifically for Malaysian residents. It accelerates the matching process, allowing users to find coaches based on preferences or specialties. Features like chat, online payments, and payment history enhance the user experience. Developed using Java via Android Studio and utilizing Firebase for data management, the project employs the Prototype modeling approach. Rigid functionality tests during the testing phase ensured all requirements were met, effectively addressing challenges faced by sport coaches and trainees in Malaysia. The application streamlines the process with an intuitive interface and robust scheduling capabilities. However, it faces limitations, including a lack of flexibility in managing sport categories and locations, and no refund policy implementation.